Draft Annual Plan 1981-82 Tamil Nadu - Planning Commission (Planning Commission, 1980)
Agriculture Minor Irrigation Soil and Water Conservation Area Development Food Animal Husbandry Dairy Development Fisheries Forests Community Development
Planning and Development Department Government of Tamil Nadu
Planning and Development Department Government of Tamil Nadu